Bridge inspection practices using non-destructive testing methods - Lee, Sangwook; Kalos, Nikolas (Journal of Civil Engineering and Management, 2015)
Non-Destructive Testing (NDT) methods have been developed and employed as a means of rapid and effective structural inspection. Despite the various kinds of NDT methods developed for bridge inspection, not much study has been performed on their usage and effectiveness at a practical level. This paper presents an evaluation of NDT methods to identify how they are implemented in state agencies in the U.S. The findings and analysis presented herein were based on the results obtained from a survey questionnaire, targeted at Departments of Transportation (DOTs) in all U.S. states and territories. The survey questionnaire was initiated to clarify multiple issues regarding NDT implementation, such as identifying the types of inspection that involve NDT methods, bridge components that are most likely to be inspected with NDT, effective methods of inspecting concrete or steel structures, and so on. A total of 40 state agencies participated in the survey processing, and the major findings obtained from the states are illustrated and explained in detail in this paper. In addition, bridge defects that are hard to detect in the course of inspection and current research efforts to develop novel NDT methods were investigated.